URGENSI DINAMIKA PERSELISIHAN HUBUNGAN INDUSTRIAL DALAM POLITIK HUKUM INDONESIA - Yusuf, Yusmedi (SUPREMASI HUKUM, 2024)
In the development of industrial relations today, there have been many problems of employment disputes caused by company conditions. Disputes over Termination of Employment are widespread and cause misery for the people to earn a living. This study uses the normative research method. Industrial disputes cause workers to experience anxiety about employment relations, have a negative impact on society because workers do not get legal protection from the government. Government policies that never side with the Indonesian people who experience industrial relations disputes often have an impact on workers. The conclusion in this writing is that the justice aspect for workers is influenced by changes in employment legislation that are more in favor of the interests of the government and companies. The government has a political interest in providing legal protection for workers, so that employment law does not achieve the goal of social justice for the welfare of workers. Keywords: Justice; Industrial Relations Disputes; Politics; Employment Law